2006
DOI: 10.1152/ajpcell.00056.2006
|View full text |Cite
|
Sign up to set email alerts
|

Muscle cell survival mediated by the transcriptional coactivators p300 and PCAF displays different requirements for acetyltransferase activity

Abstract: . Muscle cell survival mediated by the transcriptional coactivators p300 and PCAF displays different requirements for acetyltransferase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In the activation of the osteocalcin promoter by vitamin D 3 in osteoblastic cells, Sierra et al (18) demonstrated that although p300 and PCAF have additive effects on the osteocalcin promoter, the intrinsic HAT activity of p300 is dispensable. Similarly, for muscle cell differentiation and survival, the HAT activity of PCAF was required, but not that of p300 (28,43). In contrast, the HAT activity of p300 was essential for COX-2 gene transcription (36) and Notch intracellular domain signaling (37).…”
Section: Discussionmentioning
confidence: 99%
“…In the activation of the osteocalcin promoter by vitamin D 3 in osteoblastic cells, Sierra et al (18) demonstrated that although p300 and PCAF have additive effects on the osteocalcin promoter, the intrinsic HAT activity of p300 is dispensable. Similarly, for muscle cell differentiation and survival, the HAT activity of PCAF was required, but not that of p300 (28,43). In contrast, the HAT activity of p300 was essential for COX-2 gene transcription (36) and Notch intracellular domain signaling (37).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding neuronal systems in general, the FGF-system is known to play important roles in neuronal survival, axonal guidance, target recognition and maturation of neuromuscular junctions (for review see [41]); processes which are affected by SMN. In muscle, FGFs carry out muscle intrinsic functions such as muscle cell survival as well as muscle derived support of motoneuron survival [42], [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, spermatocytes, interstitial cells of adult testis and granulosa cells of the cumulus oophorus (cumulus cells) as well as mural granulosa cells in adult ovary exhibit EFhd1 expression [16,88]. EFhd1 is also expressed in IGF-II-deficient murine C2 myoblasts [89]. There, efhd1 mRNA ceases in the absence of the transcriptional co-activator p300 [89].…”
Section: Efhd1mentioning
confidence: 99%
“…EFhd1 is also expressed in IGF-II-deficient murine C2 myoblasts [89]. There, efhd1 mRNA ceases in the absence of the transcriptional co-activator p300 [89]. Healthy human renal tissue expresses efhd1 mRNA [90] and in murine kidney the collecting ducts, but not the glomeruli, reveal EFhd1 [16,88].…”
Section: Efhd1mentioning
confidence: 99%
See 1 more Smart Citation